2020
DOI: 10.1073/pnas.1920498117
|View full text |Cite|
|
Sign up to set email alerts
|

A digital media literacy intervention increases discernment between mainstream and false news in the United States and India

Abstract: Widespread belief in misinformation circulating online is a critical challenge for modern societies. While research to date has focused on psychological and political antecedents to this phenomenon, few studies have explored the role of digital media literacy shortfalls. Using data from preregistered survey experiments conducted around recent elections in the United States and India, we assess the effectiveness of an intervention modeled closely on the world’s largest media literacy campaign, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
419
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(455 citation statements)
references
References 37 publications
22
419
3
11
Order By: Relevance
“…A practical application of inoculation theory in the context of COVID-19 misinformation is the new online game, Go Viral!, 2 developed in collaboration with the United Kingdom government and the WHO in which players learn to resist three manipulation techniques commonly used to spread misinformation about the coronavirus: fearmongering, the use of fake experts, and conspiracy theories. An open question in active inoculation research is the extent to which inoculation can boost truth-discernment skills, that is, not just the ability to spot and resist misinformation attacks but also the ability to better identify real or credible news (Guess et al, 2020;Roozenbeek et al, 2020a). Compton et al (2016) called for more "work that pushes forward our understanding of persuasion and has applied value as a health messaging strategy to help combat serious threats to healthy living" (p. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A practical application of inoculation theory in the context of COVID-19 misinformation is the new online game, Go Viral!, 2 developed in collaboration with the United Kingdom government and the WHO in which players learn to resist three manipulation techniques commonly used to spread misinformation about the coronavirus: fearmongering, the use of fake experts, and conspiracy theories. An open question in active inoculation research is the extent to which inoculation can boost truth-discernment skills, that is, not just the ability to spot and resist misinformation attacks but also the ability to better identify real or credible news (Guess et al, 2020;Roozenbeek et al, 2020a). Compton et al (2016) called for more "work that pushes forward our understanding of persuasion and has applied value as a health messaging strategy to help combat serious threats to healthy living" (p. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further complications arise from the "continued influence effect" of misinformation, which states that people may continue to believe misinformation even after it has been debunked (Ecker et al, 2010;Lewandowsky et al, 2012). In addition, while media literacy initiatives are important and can be effective under the right conditions (Bode and Vraga, 2015;Guess et al, 2020;Van Bavel et al, 2020), they are often expensive to develop, slow to roll out, and reactive rather than proactive.…”
Section: Leveraging Insights From Psychology: Inoculating Against Covmentioning
confidence: 99%
“…Using actual true and false content from social media is particularly important if one wants to make the argument that their favored intervention is likely to have an impact if implemented in the real world. This research has looked at factors such as fact-checking (Pennycook, Bear, Collins, & Rand, 2020), emphasizing news sources/publishers (Dias, Pennycook, & Rand, 2020), digital media literacy tips (Guess et al, 2020), and subtly prompting people to think about accuracy to improve sharing decisions (Pennycook, Epstein, et al, 2020;Pennycook, McPhetres, et al, 2020).…”
Section: Figure 1 Examples Of Fake/false (Top) and Real/mainstream/tmentioning
confidence: 99%
“…And constraints on time and resources put pressure on professional fact-checkers to keep up with the latest "fake news" stories before they hit social media. For these reasons, social scientists have increasingly turned to prebunking rather than debunking strategies (van der Linden 2019; Guess et al 2020). In other words, they seek to equip citizens with broadly applicable tools to recognize "fake news" stories in order to prevent belief and sharing, instead of correcting beliefs after the damage is already done.…”
mentioning
confidence: 99%
“…Elderly social media users -arguably due to shortfalls in digital media literacy and a failure to discern "fake" from "real" online -are among the worst offenders when it comes to sharing "fake news" on multiple social media platforms (Guess, Nagler and Tucker 2019;Osmundsen et al 2020). Finally, Guess et al (2020) recently demonstrated that exposure to Facebook's "Tips to Spot False News," a short list of simple tools for identifying misleading news, improved the ability to discern between false and mainstream news story headlines; an improvement that remained measurable more than two weeks later after the intervention.…”
mentioning
confidence: 99%